FROM TRADITION TO ENTREPRENEURSHIP: GENDER TRANSFORMATION AND WOMEN'S AGENCY IN GIRILOYO BATIK VILLAGE - Derfiora, Amalia Desi; Hidayah, Sita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study analyzes in depth how gender transformation and women's entrepreneurial agency developed in Giriloyo Batik Village, historically bound by traditional gender norms confining women to the domestic sphere and lacking recognition of economic value. The aim is to understand how external factors trigger social change, women's role negotiation strategies, and the cultural impact on household gender relations. Using a qualitative ethnographic approach, the study employs in-depth interviews with women entrepreneurs and participatory observation to identify social change patterns. Key findings reveal two catalysts: (1) the 2006 earthquake crippling men's public livelihoods, and (2) UNESCO's batik recognition granting global legitimacy. Women in Giriloyo employed subtle negotiation, transforming batik-making into institutionalized economic production via independent businesses and cooperatives, bolstered by Javanese work ethic. This led to greater bargaining power and limited autonomy in family decisions. The novelty argues that the double burden can become an effective strategy for social and economic recognition without challenging patriarchal norms directly.